THE DESCRIPTIVE STUDY OF SELF-DIRECTED LEARNER IN SPEAKING ENGLISH AT NON-ENGLISH DEPARTMENT IN IAIN SULTAN AMAI GORONTALO - Amrain Mahmud (Al-Lisan: Jurnal Bahasa, 2017)
Speaking ability is to express the idea and thought by orally in class context, school, and surroundings. But, speaking ability will be difficult if not unstinting. Self-Directed Learning are increase knowledge, skill, accomplishment, or personal development that an individual selects and brings about by his or her own efforts using any method, in any circumstances, at any time. The aim this research is To describe how the ways self-directed learners in speaking English done by Non-English Department. The subjects of research are five students Non English Department 2nd semester of Perbankan Syariah in IAIN Sultan Amai Gorontalo by using qualitative method and collected data by using interview unstructured and documentation. The result of research that is self-directed learning of students in speaking English ability is by doing the element essential of self-directed learning.